THE INFLUENCE OF LEARNING MOTIVATION AND VOCABULARY MASTERY TOWARDS WRITING NARATIVE TEXT ACHIEVEMENT - Elis Solihat; Hanna Sundari (Universitas Indraprasta PGRI, 2018)
ABSTARCT: The purpose of this study was to determine the effect of learning motivation and vocabulary mastery together on the ability to write English narrative on private junior high school students in Bogor city, the influence of learning motivation on the ability to write English narrative on private Junior High School students in Bogor city, and the influence of mastery vocabulary on the ability to write English narrative in private Junior High School students in Bogor city. Respondents in this study amounted to 90 students who were randomly selected in several private Junior High Schools in Bogor city. The research method used is a survey method with three variables, namely learning motivation (X1), vocabulary mastery (X2), and English narrative writing ability (Y). The results showed: 1) There was a significant influence of learning motivation and vocabulary mastery together on the ability to write English narrative for private Junior High School students in Bogor city. This is evidenced by the acquisition of Sig. 0,000 <0,05 and fh = 13,905. 2) There is a significant effect of learning motivation on the ability to write English narrative for private Junior High School students in Bogor city. This is evidenced by the acquisition of Sig. 0,000 <0.05 and th = 3,764. 3) There is a significant influence on vocabulary mastery on the ability to write English narrative for private Junior High School students in the Bogor city. This is evidenced by the acquisition of Sig. 0.011 <0.05 and th = 2.600. From the results of the research obtained, it can be recommended that learning motivation and good vocabulary mastery are needed to achieve the ability to write narrative in English. Keyword: learning motivation, vocabulary mastery, to write English Narrative ABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh motivasi belajar dan penguasaan kosakata secara bersama-sama terhadap kemampuan menulis naratif bahasa Inggris pada siswa SMP Swasta di Kota Bogor, pengaruh motivasi belajar terhadap kemmapuan menulis naratif bahasa Inggris pada siswa SMP Swasta di Kota Bogor, dan pengaruh penguasaan kosakata terhadap kemampuan menulis naratif bahasa Inggris pada siswa SMP Swasta di Kota Bogor. Responden dalam penelitian ini berjumlah 90 orang siswa yang dipilih secara random pada beberapa sekolah SMP Swasta di Kota Bogor. Metode penelitian yang digunakan adalah metode survei dengan tiga variabel yaitu Motivasi belajar (X1), Penguasaan kosakata (X2), dan Kemampuan menulis naratif bahasa Inggris (Y). Hasil penelitian menunjukan: 1)Terdapat pengaruh yang signifikan motivasi belajar dan penguasaan kosakata secara bersama-sama terhadap kemampuan menulis naratif bahasa Inggris siswa SMP Swasta di Kota Bogor. Hal ini dibuktikan dengan perolehan nilai Sig. 0,000 < 0,05 dan Fh = 13, 905. 2) Terdapat pengaruh yang signifikan motivasi belajar terhadap kemampuan menulis naratif bahasa Inggris siswa SMP Swasta di Kota Bogor. Hal ini dibuktikan dengan perolehan nilai Sig. 0,000 < 0,05 dan th = 3,764. 3) Terdapat pengaruh yang signifikan penguasaan kosakata terhadap kemampuan menulis naratif bahasa Inggris siswa SMP Swasta di Kota Bogor. Hal ini dibuktikan dengan perolehan nilai Sig. 0,011 < 0,05 dan th = 2,600. Dari hasil penelitian yang diperoleh dapat direkomendasikan bahwa untuk mencapai kemampuan menulis naratif bahasa Inggris diperlukan motivasi belajar dan penguasaan kosakata yang baik. Kata Kunci: Motivasi belajar, penguasaan kosakata, menulis naratif bahasa Inggris